Rear view of the Garbhagriha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The southwest elevation view of the garbhagriha (sanctum sanctorum) of the Hazareshwar Temple offers a glimpse of the vertical axis, where every detail is meticulously crafted. As one observes this sacred space from behind, a sense of reverence envelops the observer, drawn to the harmonious alignment of architectural elements ascending skyward. Each component of the temple’s adornment, from the intricately carved walls to the tapering shikhara (superstructure), contributes to the overall beauty and structure of the temple.